EFEKTIVITAS PENGADAAN BARANG DAN JASA SECARA ELEKTRONIK (E-PROCUREMENT) PADA LPSE KOTA PEKANBARU - Utari Swadesi; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is based on the phenomenon is still often the occurrence of corruption, collusion and nepotism (KKN) practices of goods and services by the government. So that e-procurement can be an instrument to prevent and reduce corruption, collusion and nepotism (KKN) because through e-procurement program, procurement of goods and services can further improve transparency and accountability, increase market access and fair business competition, Improve the efficiency of the procurement process, support monitoring and auditing processes, and meet real-time information access needs. So the purpose of this study is to know the effectiveness of procurement of goods and services electronically (e-procurement) on LPSE Pekanbaru and to determine the factors that affect the effectiveness of procurement of goods and services electronically (e-procurement) on LPSE Pekanbaru.The concept of theory used is effectiveness, which Mahmudi proposes. This research uses qualitative research methods with descriptive data assessment. In the data collecting researchers using interviewing techniques, observation and documentation. By using key informant as source of information and technique of tringulation as source in testing of data validity.The results of this study by using e-procurement program in the procurement of goods and services within Pekanbaru city government has not been implemented effectively. Because this is due to limited human resources (HR), technical difficulties and limited funding. Which all these factors greatly affect the effectiveness of procurement of goods and services electronically (e-procurement) on LPSE Pekanbaru.Keywords: Effectiveness, E-Procurement, LPSE